2015
DOI: 10.1002/rcm.7182
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric solid analysis probe mass spectrometry vs electrospray tandem mass spectrometry of polydimethylsiloxanes in positive and negative ionization modes

Abstract: Atmospheric solid analysis probe mass spectrometry vs electrospray tandem mass spectrometry of polydimethylsiloxanes in positive and negative ionization modes Atmospheric solid analysis probe [1] (ASAP) has been found to be promising for the analysis of polymers exhibiting poor electrospray ionization (ESI) efficiency.[2] Due to pyrolysis processes in ASAP, [3] polymers undergo extensive fragmentation and the resulting fragment ions are limited to the low m/z range.[2] Single-stage ASAP-MS would thus have some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Fouquet et al compared ASAP-MS with ESI-MS/MS and found the methods to be complementary for polydimethylsiloxanes with M w between 18 000 and 110 000 due to the fragmentation produced during the ASAP thermal vaporization and ionization processes. 104 ASAP IMS-MS was evaluated as a method to characterize poly(ether ether ketone) polymers by Cossoul et al 105 This solvent-free approach produced almost identical end group assignments and relative ion abundances as MALDI which, unlike ASAP, requires use of strong solvents such as sulfuric acid to first dissolve the polymer. A cyclic olefin copolymer grafted with aryl layers was characterized by Vieillard et al using ASAP in combination with IMS-MS among other analytical methods.…”
Section: ■ Discharge-based Ambient Ionizationmentioning
confidence: 99%
“…Fouquet et al compared ASAP-MS with ESI-MS/MS and found the methods to be complementary for polydimethylsiloxanes with M w between 18 000 and 110 000 due to the fragmentation produced during the ASAP thermal vaporization and ionization processes. 104 ASAP IMS-MS was evaluated as a method to characterize poly(ether ether ketone) polymers by Cossoul et al 105 This solvent-free approach produced almost identical end group assignments and relative ion abundances as MALDI which, unlike ASAP, requires use of strong solvents such as sulfuric acid to first dissolve the polymer. A cyclic olefin copolymer grafted with aryl layers was characterized by Vieillard et al using ASAP in combination with IMS-MS among other analytical methods.…”
Section: ■ Discharge-based Ambient Ionizationmentioning
confidence: 99%
“…Since 2005, ASAP has grown in popularity since it permits the direct analysis of a wide range of samples and in particular polymers. [29][30][31][32][33] For instance, synthetic polymers have been efficiently analysed using ASAP and their polydispersity evaluated. 34 More recently, a rapid characterization of various polyalphaolefin samples was reported using ASAP coupled with ion mobility spectrometry -mass spectrometry (IMS-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional pyrolysis probes, the ASAP source is operated at relatively low temperatures (≤500 °C), yielding not only monomeric but also oligomeric species that provide molecular connectivity detail. Further microstructural verification and complementary information on the thermal stability and degradation pathways of the polymer can be gained by tandem mass spectrometry (MS/MS) experiments. In the past 13 years, ASAP-MS and ASAP-MS/MS have been used extensively to characterize polymer additives as well as diverse, relatively low molecular weight synthetic polymers, including PEG, polystyrene, PU, and PDMS . An ASAP source combined with ion mobility (IM)-MS adds potential to separate desorbate and degradant ions by their size and shape, thus enhancing the analytical information obtainable from mild thermal degradation experiments. The added IM dimension enables the separation of isobaric and isomeric species and also permits determination of their collision cross-section (CCS) values, which provide a quantitative insight about their 3D size/shape.…”
Section: Introductionmentioning
confidence: 99%
“…39−41 In the past 13 years, ASAP-MS and ASAP-MS/MS have been used extensively to characterize polymer additives as well as diverse, relatively low molecular weight synthetic polymers, 44−48 including PEG, 45 polystyrene, 45 PU, 47 and PDMS. 48 An ASAP source combined with ion mobility (IM)-MS adds potential to separate desorbate and degradant ions by their size and shape, 49−51 thus enhancing the analytical information obtainable from mild thermal degradation experiments. 52−57 The added IM dimension enables the separation of isobaric and isomeric species and also permits determination of their collision cross-section (CCS) values, which provide a quantitative insight about their 3D size/shape.…”
Section: ■ Introductionmentioning
confidence: 99%